Revision of the genus Xylodrypta Lesne 1901 (Coleoptera: Bostrichidae: Bostrichinae: Xyloperthini) with a new species and a key to species - Liu, Lan-Yu; Beaver, Roger A.; Sanguansub, Sunisa (Zootaxa, 2021)
We revise the monospecific bostrichid genus Xylodrypta Lesne 1901, and describe a new species, X. lanna Liu & Beaver from Thailand and Laos. A key is given to distinguish the two species of Xylodrypta.